Two-Year Follow-Up of Patients With Atrial Fibrillation Receiving Edoxaban in Routine Clinical Practice: Results From the Global ETNA-AF Program - De Caterina, Raffaele; Unverdorben, Martin; Chen, Cathy; Choi, Eue-Keun; Koretsune, Yukihiro; Morrone, Doralisa; Pecen, Ladislav; Bramlage, Peter; Wang, Chun-Chieh; Yamashita, Takeshi; Kirchhof, Paulus (Clinical cardiology, 2025)
BACKGROUND: Randomized clinical trials demonstrated similar efficacy and improved safety of direct oral anticoagulants versus warfarin in patients with atrial fibrillation (AF). Long-term data in routine clinical practice are needed. HYPOTHESIS: Patients with AF receiving edoxaban at baseline continue to have low annualized effectiveness and safety event rates in the second year of follow-up, with regional variations observed. METHODS: The Global ETNA-AF program is a prospective, noninterventional study of patients with AF receiving edoxaban. Patient characteristics and annualized clinical event rates were assessed overall and by region across the 2-year follow-up. Annualized event rates of bleeding and thromboembolic events were assessed within the first year and conditionally in patients who were event-free up to 12 months in the second year. RESULTS: This analysis comprised 26 805 patients from Europe (n = 13 164), Japan (n = 10 342), and non-Japanese Asian regions (n = 3299). Patients from Europe had the highest burden of comorbidities. The annualized event rates for major bleeding, any stroke, all-cause death, and cardiovascular death varied by region. The global annualized event rates in the first and second year were 1.31%/year and 0.86%/year for major bleeding, 1.06%/year and 0.65%/year for any stroke, 0.84%/year and 0.73%/year for cardiovascular death, and 3.05%/year and 3.18%/year for all-cause death. CONCLUSION: Annualized event rates for any stroke and major bleeding remained low through 2-year follow-up for patients with AF receiving edoxaban at baseline. Differences in annualized event rates for all-cause and cardiovascular mortality between Europe, Japan, and non-Japanese Asian regions may reflect variations in baseline characteristics. TRIAL REGISTRATION: Europe, NCT02944019; Japan, UMIN000017011; Korea/Taiwan, NCT02951039; Hong Kong, NCT03247582; and Thailand, NCT03247569.
Keywords: pyridiny; Female; Europe; Atrial Fibrillation; výsledek terapie; ženské pohlaví; Thiazoles; cévní mozková příhoda; thiazoly; Time Factors; časové faktory; krvácení; lidé; Evropa; Stroke; Treatment Outcome; Aged, 80 and over; následné studie; Risk Factors; Incidence; tromboembolie; prospektivní studie; Follow-Up Studies; Male; Factor Xa Inhibitors; incidence; Prospective Studies; Aged; inhibitory faktoru Xa; Pyridines; Hemorrhage; rizikové faktory; fibrilace síní; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Thromboembolism; Middle Aged; Humans